2011
DOI: 10.1038/hr.2010.263
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of hypertension to diabetic nephropathy and retinopathy: the role of inflammation and oxidative stress

Abstract: Diabetes and hypertension frequently coexist and constitute the most notorious combination for the pathogenesis of diabetic nephropathy and retinopathy. Large clinical trials have clearly demonstrated that tight control of glycemia and/or blood pressure significantly reduces the incidence and progression of diabetic retinopathy (DR) and nephropathy. However, the mechanism by which hypertension interacts with diabetes to induce and/or exacerbate nephropathy and retinopathy is very unclear. Substantial evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 153 publications
(190 reference statements)
1
38
0
Order By: Relevance
“…Previous studies describing retinopathy in dogs with naturally occurring diabetes have reported similar prevalence values as this study, ranging from 3 to 21% 5, 7, 29, 30. Although hypertension is also a well‐known risk factor for development and progression of diabetic retinopathy in humans,28, 31 a similar correlation was not found in the present study. Time since DM diagnosis and glycemic control scores were also not correlated with presence of ophthalmoscopically visible retinopathy in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies describing retinopathy in dogs with naturally occurring diabetes have reported similar prevalence values as this study, ranging from 3 to 21% 5, 7, 29, 30. Although hypertension is also a well‐known risk factor for development and progression of diabetic retinopathy in humans,28, 31 a similar correlation was not found in the present study. Time since DM diagnosis and glycemic control scores were also not correlated with presence of ophthalmoscopically visible retinopathy in this study.…”
Section: Discussionsupporting
confidence: 88%
“…The diabetic rats either did or did not receive tempol treatment (Calbiochem, La Jolla, Calif., USA), as previously reported [7]. We have chosen to use SHR rats because others and we have shown that diabetic SHR display features of accelerated nephropathy and also because of the frequent association of hypertension with DM in human DN [8,9]. …”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, one essential mechanism seems to be oxidative stress, which mediates glomerular and interstitial damage in diabetic nephropathy [9,10,11]. Indeed, oxidative stress was detected in murine mesangial and proximal tubular epithelial cells, in rats and in patients with hyperglycemia, suggesting that oxidative stress may play a pathological role in the development of diabetic nephropathy [12,13]. …”
Section: Introductionmentioning
confidence: 99%